Gender differences in risk-taking attitudes among adolescents - Hanapi, Nur Nadia; Daud, Mohd Najmi; Mansor, Mariani (Secholian Publication, 2019)
Issues concerning risk taking attitude and behaviors among adolescents in Malaysia has become increasingly complex and challenging. This paper aims to examine the gender differences in risk-taking attitude among adolescents in Malaysia. 426 adolescents consisting of 183 boys (43%) and 243 girls (51.9 %) participated in this study. Data were obtained using a self-administered questionnaire namely the Attitude towards risk questionnaire (Franken, Gibson & Rowland, 1992). The findings suggested that there is a significant difference between male and female with respect to risk taking attitude, t (424) = 3.14, p = .03 (two-tailed). The analysis of mean further revealed that male adolescents (M = 53.85. SD = 11.99) is inclined towards risk attitudes compared to female adolescents (M =50.14, SD=13.39). Apart from verifying the previous findings on the gender differences in risk taking attitudes, the present finding indicates the need for a gender specific approach to the assessment and intervention of risk-taking attitude among adolescents in Malaysia.